Risk of Nongenitourinary Cancers in Patients With Spinal Cord Injury: A Population-based Cohort Study. Issue 2 (January 2016) - Kao, Chia-Hong; Sun, Li-Min; Chen, Yueh-Sheng; Lin, Cheng-Li; Liang, Ji-An; Kao, Chia-Hung; Weng, Ming-Wei
Abstract : Abstract: Little information is available regarding the risk of nongenitourinary (GU) cancers in patients with spinal cord injury (SCI). The authors conducted a nationwide population-based study to investigate whether a higher risk of non-GU cancer is seen among patients with SCI. Data retrieved from the National Health Insurance Research Database of Taiwan were used in this study. A total of 41, 900 patients diagnosed with SCI between 2000 and 2011 were identified from the National Health Insurance Research Database and comprised the SCI cohort. Each of these patients was randomly frequency matched with 4 people from the general population (without SCI) according to age, sex, comorbidities, and index year. Cox proportional hazards regression analysis was used to calculate adjusted hazard ratios and 95% confidence intervals and determine how SCI affected non-GU cancer risk. No significant difference in overall non-GU cancer risk was observed between the SCI and control groups. The patients with SCI exhibited a significantly higher risk of developing esophageal, liver, and hematologic malignancies compared with those without SCI. By contrast, the SCI cohort had a significantly lower risk of colorectal cancer compared with the non-SCI cohort (adjusted hazard ratio = 0.80, 95% confidence interval = 0.69–0.93). Additional stratified analyses by sex, age, and follow-up duration revealed various correlations between SCI and non-GU cancer risk. The patients with SCI exhibited higher risk of esophageal, liver, and hematologic malignancies but a lower risk of colorectal cancer compared with those without SCI. The diverse patterns of cancer risk among the patients with SCI may be related to the complications of chronic SCI.